2005
DOI: 10.1097/01.psy.0000181273.74398.d7
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Associated With Cancer History and BRCA1/2 Genetic Testing

Abstract: Results from this study suggest that both personal and family cancer diagnoses can be significant stressors for a subset of high-risk women. Rates of threshold and subthreshold PTSD related to genetic testing appear to be less common, although carriers may be at higher risk for significant posttraumatic symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 58 publications
3
20
1
1
Order By: Relevance
“…Although several comprehensive reviews and long-term studies suggest that adverse psychological consequences of cancer GC and testing are uncommon (Braithwaite, Emery, Walter, Prevost, & Sutton, 2004;Broadstock, Michie, & Marteau, 2000;Butow, Lobb, Meiser, Barratt, & Tucker, 2003;Lerman, Croyle, Tercyak, & Hamann, 2002;Meiser, 2005;van Oostrom et al, 2003), there has been a suggestion in the literature that certain women affected with cancer are at increased risk for distress subsequent to the counseling and testing process. This group may be especially at risk if they are undergoing GC and testing at a time near the cancer diagnosis and treatment process (Hamann, Somers, Smith, Inslicht, & Baum, 2005;Lerman et al, 2002;Meiser, 2005). Although a few studies have examined the impact of GC and testing on decisions related to breast cancer treatment in this group (Schwartz et al, 2005;Weitzel et al, 2003), there is little information about whether psychosocial distress among recently diagnosed breast cancer patients may interfere with the goals of GC such as reducing psychosocial distress, aiding in decision making, and promoting psychosocial well-being.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although several comprehensive reviews and long-term studies suggest that adverse psychological consequences of cancer GC and testing are uncommon (Braithwaite, Emery, Walter, Prevost, & Sutton, 2004;Broadstock, Michie, & Marteau, 2000;Butow, Lobb, Meiser, Barratt, & Tucker, 2003;Lerman, Croyle, Tercyak, & Hamann, 2002;Meiser, 2005;van Oostrom et al, 2003), there has been a suggestion in the literature that certain women affected with cancer are at increased risk for distress subsequent to the counseling and testing process. This group may be especially at risk if they are undergoing GC and testing at a time near the cancer diagnosis and treatment process (Hamann, Somers, Smith, Inslicht, & Baum, 2005;Lerman et al, 2002;Meiser, 2005). Although a few studies have examined the impact of GC and testing on decisions related to breast cancer treatment in this group (Schwartz et al, 2005;Weitzel et al, 2003), there is little information about whether psychosocial distress among recently diagnosed breast cancer patients may interfere with the goals of GC such as reducing psychosocial distress, aiding in decision making, and promoting psychosocial well-being.…”
Section: Discussionmentioning
confidence: 96%
“…Women undergoing GC and testing at a time near cancer diagnosis and treatment may be at increased risk for distress subsequent to the counseling and testing process (Hamann et al, 2005;Lerman, et al, 2002;Meiser 2005). Although a few studies have examined the impact of GC and testing on decisions related to breast cancer treatment in this group (Schwartz et al, 2005;Weitzel, et al, 2003), there is little information about whether psychosocial distress among recently diagnosed breast cancer patients may interfere with the goals of GC such as reducing psychosocial distress, aiding in decision making, and promoting psychosocial well-being (Vadaparampil, Miree, Wilson, & Jacobsen, 2007).…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…Although some women report no adverse effects of genetic testing [17,18] women's psychological responses to testing are highly variable, and the genetic testing experience has the potential to generate distress and worry among some participants. For example, anticipating genetic test results led to increased anxiety among some women [19], and receiving a mutation-positive test result has been linked to a short-term increase in test-related distress [20] as well as elevated risk of posttraumatic stress disorder [17]. Receiving information that one carries a genetic predisposition to breast and ovarian cancer shares important features with receiving a cancer diagnosis, as it conveys the prospect of a future cancer diagnosis and the associated mortality threat, life disruption, and other negative psychological sequelae [21,22].…”
Section: Introductionmentioning
confidence: 98%
“…Women who are identified as carriers of a BRCA1 or BRCA2 mutation have a 55-85% lifetime risk of developing breast cancer, 23-63% lifetime risk of developing ovarian cancer, and up to a 95% chance of developing either cancer before age 70 [15,16]. Although some women report no adverse effects of genetic testing [17,18] women's psychological responses to testing are highly variable, and the genetic testing experience has the potential to generate distress and worry among some participants. For example, anticipating genetic test results led to increased anxiety among some women [19], and receiving a mutation-positive test result has been linked to a short-term increase in test-related distress [20] as well as elevated risk of posttraumatic stress disorder [17].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown marked anticipatory anxiety among those awaiting test results for various conditions or disease predispositions, 39 -43 though fewer have found evidence of significant psychological symptoms or emotional upset after testing, even for those found to be carriers. 44,[45][46][47][48] To date, most of the literature on pre-and post-genetic testing-related distress had focused either on those who knew of increased risk (e.g., for hereditary cancers or Huntington disease) prior to testing, 49 or on those found to have possibly increased fetal risk during pregnancy. 50 Given that in the future, population screening for many late-onset disorders may reveal more genotypes with low or unclear risk than those clearly associated with disease, it is important to understand how people perceive and react to this type of result.…”
Section: Discussionmentioning
confidence: 99%